2018
DOI: 10.3389/fmicb.2018.00208
|View full text |Cite
|
Sign up to set email alerts
|

Flagellar Basal Body Structural Proteins FlhB, FliM, and FliY Are Required for Flagellar-Associated Protein Expression in Listeria monocytogenes

Abstract: Listeria monocytogenes is a food-associated bacterium that is responsible for food-related illnesses worldwide. In the L. monocytogenes EGD-e genome, FlhB, FliM, and FliY (encoded by lmo0679, lmo0699, and lmo0700, respectively) are annotated as putative flagella biosynthesis factors, but their functions remain unknown. To explore whether FlhB, FliM, and FliY are involved in Listeria flagella synthesis, we constructed flhB, fliM, fliY, and other flagellar-related gene deletion mutants using a homologous recombi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 49 publications
(62 reference statements)
1
15
0
Order By: Relevance
“…Studies of the functions of flagellar-related proteins in L. monocytogenes are in the preliminary stage. Although the characteristic tumbling motility of L. monocytogenes was observed in all of our 27 isolates, the flaA gene was not detected from four of these motile isolates, stipulating that there are alternative mechanisms controlling the flagella and the secretion of other flagella-related proteins involved in the synthesis of the L. monocytogenes flagellum required for its motility and the secretion of supplementary flagellar-related proteins [60]. Attachment and formation of biofilm allows the colonization of surfaces, including food processing environments [61].…”
Section: Discussionmentioning
confidence: 61%
“…Studies of the functions of flagellar-related proteins in L. monocytogenes are in the preliminary stage. Although the characteristic tumbling motility of L. monocytogenes was observed in all of our 27 isolates, the flaA gene was not detected from four of these motile isolates, stipulating that there are alternative mechanisms controlling the flagella and the secretion of other flagella-related proteins involved in the synthesis of the L. monocytogenes flagellum required for its motility and the secretion of supplementary flagellar-related proteins [60]. Attachment and formation of biofilm allows the colonization of surfaces, including food processing environments [61].…”
Section: Discussionmentioning
confidence: 61%
“…Although FlhB is generally regarded as a class 2 flagellar biosynthetic protein ( 46 ), recently flhB was reported to regulate the expression of several flagellar genes, including flaA (O157 fliC homolog), fliY , fliS , motA , lmo0695 , and lmo0698 , in Listeria monocytogenes ( 17 ). Hence, we performed qRT-PCR to determine whether flhB regulates the expression of flagellar genes in O157.…”
Section: Resultsmentioning
confidence: 99%
“…Class 3 encodes components for filament assembly and motor function, including the flagellin gene, fliC . FlhB is a class 2 constituent membrane protein of the basal body required for flagellar appendant synthesis and hook-length control involved in substrate specificity switch ( 17 , 18 ). Recently, FlhB was found to regulate flagellar gene expression in Listeria monocytogenes ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Lm 568 downregulated fliY (lmo0693, flagellar motor switch protein), while Lm 08-5578 downregulated the chemotaxis protein lmo1699 ( Supplementary Table S2). A study by Cheng et al (2018) showed how in the absence of either FlhB, FliM or FliY L. monocytogenes completely lost its ability to produce flagella. Downregulation of motility genes in response to desiccation have also been observed in Pseudomonas putida (Van de Mortel and Halverson, 2004) and Enterobacter sakazakii (Riedel and Lehner, 2007).…”
Section: Desiccation Decreases Expression Of Genes Involved In Motilimentioning
confidence: 99%